Estratégia de planejamento e otimização do handover em redes móveis densificadas - SILVA, Ketyllen da Costa (Universidade Federal do Pará, 2018)
The increase in mobile devices and applications in recent years has led to an overload of the network infrastructure responsible for disposing this traffic, thus affecting the performance of the network as the user experience.Heterogeneous mobile networks are already a reality and their densification has been put forward as one of the suggested solutions to meet the expected demands for 5th generation (5G) mobile networks. However, in the current networks, it is still common for fixed parameters to be used for the configuration of the network although this strategy does not always prove to be efficient. It is within this context that the concept of selforganizing networks (SONs) has been established, in which several network parameters are automatically adjusted on the basis of measurements and intelligent systems in real time. This thesis presents a strategy to optimize the handover in LTE networks with dense small cells. Based on measurements and fuzzy logic new algorithms are proposed for self-tuning network parameters. From discrete simulation using MATLAB, the results are evaluated and presented through the main performance metrics of handover.